Best Management Practices in the Everglades Agricultural Area: Fertilizer Spill Prevention - Orlando A. Diaz; Samira H. Daroub; Ronald W. Rice; Timothy A. Lang; Ming Chen (EDIS)
Phosphorus fertilizer spill prevention is a Best Management Practice (BMP) approved by the South Florida Water Management District (SFWMD), one designed to reduce drainage P loads in the Everglades Agricultural Area (EAA). Spill prevention of P fertilizers is a BMP that is widely implemented by growers in the EAA. This BMP is easily implemented and can have an immediate impact on reducing off-farm P loads. This EDIS document is part of a series of publications that provide current implementation guidelines for commonly employed farm-level BMPs designed to reduce P loads from farms located within the EAA basin. This document is SL231, one of a series of the Department of Soil and Water Sciences, UF/IFAS Extension. Original publication date September 2005.